The impact of country level factors on the choice of R&D offshoring location - Materlínová, Eva (2021)
The objective of this bachelor thesis on the topic of “The Impact of Country Level Factors on the Choice of R&D Offshoring Location” was to understand what determinants are considered the most by companies when offshoring R&D, as well as their impact on the choice of offshoring location. The reason for this objective was that offshoring to a country without a research or with badly conducted research could lead to a great loses for a company and so it is crucial to understand the factors which define business conditions of a country. Moreover, as there is a new trend which not only propels companies to offshore R&D to emerging markets, but to also prioritize the availability of talent over cost effectiveness, the objective is also to verify and explain this tendency. The work is divided into two parts. The first theoretical part draws on the literature research, defines and explains the basic concepts associated with R&D offshoring, describes the offshoring phenomenon and outlines the country-level factors. On the contrary, the practical part analyses the main factors taken into consideration by the companies IBM and Punch, when offshoring their R&D activities. The research was conducted in the form of semi-structured interview with the managers of both companies. Based on the interview analysis, it was found out that both companies considered the availability of talented workforce as the most important factor which determined the site of R&D offshoring. The second most important factor was price so as to ensure competitiveness on the market. The companies choices were also strongly influenced by government incentives and market regulations.